The Epidemiological Characteristics of Coronavirus Disease (COVID-19) in Halabja Province/Kurdistan –Iraq - Shareef, Osama Hamid; Mohammed, Othman Abdulrahman; Ghafor, Dashty Aziz; Ali, Ari Shareef; Baqi, Hardi Rafat; Ali, Ali Aziz; Faraj, Aryan Mahmood; Qadir, Syamand Ahmed; Omar Aljabary, Ali Muhi Aldeen (Kurdistan Journal of Applied Research, 2022)
The new highly transmitted pathogenic viral infection started from Wuhan, China at the end of 2019. The World Health Organization publicized that it is phylogenetically belonging to severe acute respiratory syndrome (SARS), introduced as COVID-19 pandemic disease, and spread around the world. The first confirmed case in Kurdistan region was on 1st of March, 2020. While the first COVID-19 case in Halabja province/Kurdistan region was recorded on 27th of March, 2020. This study was designed, when the Wafa Hospital constructed in Halabja/Kurdistan region for infected patients. The data were collected from 14th April to the end of December, 2020 and included name and age of the infected persons. Samples were obtained nasopharyngeal using a sterilized swab following WHO guidelines and then the real time PCR (RT-PCR) machine was used for analysis. This study was particularly representing the impact of COVID-19 on suspected person. It was focused on the susceptibility of suspected cases in Halabja province, according to ages and sexes. During the study, 5183 cases were tested, 2796 (54%) cases were confirmed as positive result and 2387 (46%) cases were negative, including all ages, males and females. Confirmed male cases among 3116 cases were 1646 (60.1%), and 1150 (39.9%) positive cases recorded among 2067 female tests. In addition, the ages of the tested cases were divided into 10 sub-groups (0-9) years old to (90-99) years old, subsequently. The result of this study for both sexes, revealed that, the most confirmed cases among (30-39) years group and (40-49) years group were (1521) and (1223) confirmed positive cases. The lowest cases were among over 80 years old and below 9 years old (10, 3) confirmed cases. Besides, the confirmed cases for other age groups for both sexes were (50-59) years old was 397, (60-69) years old was 205, (70-79) was 77. Finally, the data showed that, the common confirmed cases were among groups 20-59 years old and the rare cases were under 9 and over 80 years.